1998
DOI: 10.1210/endo.139.3.5815
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Identification of Proteins Related to the Hereditary Dwarfism of the rdw Rat*

Abstract: Proteins having relations to hereditary dwarfism of the rdw rat (gene symbol: rdw) were searched for in various tissues of the rat with an improved two-dimensional gel electrophoresis technique followed by immunoblotting and microsequencing. Tissues inspected were cerebral cortex, cerebellum, brain trunk, hypothalamus, pituitary, thyroid gland, liver, testis, spleen, and thymus. Only pituitary and thyroid glands among those tissues showed abnormalities in protein contents. GH and PRL contents in the rdw pituit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Based on the findings of in this study, and the results of our previous studies, such as protein analysis [17], morphological findings [19], and sequencing of the entire Tg cDNA from the rdw rat [9,12], we concluded that the synthesized abnormal Tg forms a complex with the chaperons and accumulates in the ER, resulting in dramatic swelling of the ER. As a result, the rdw rat has severe hypothyroidism and dwarfism.…”
Section: Figsupporting
confidence: 60%
See 2 more Smart Citations
“…Based on the findings of in this study, and the results of our previous studies, such as protein analysis [17], morphological findings [19], and sequencing of the entire Tg cDNA from the rdw rat [9,12], we concluded that the synthesized abnormal Tg forms a complex with the chaperons and accumulates in the ER, resulting in dramatic swelling of the ER. As a result, the rdw rat has severe hypothyroidism and dwarfism.…”
Section: Figsupporting
confidence: 60%
“…Subsequently, it was revealed that the expressions of mRNA (Received 28 February 2005 / Accepted 1 September 2005 Address corresponding: S. Furudate, Department of Laboratory Animal Science, Japan of growth hormone (GH) and prolactin (PRL) in the rdw rat are drastically decreased [18,21]. In addition, the GH and PRL proteins in the rdw rat are decreased to a level 1/30 to 1/100 of those of a normal rat [17,18].In the rdw rat, the thyroxine (T 4 ) levels in serum are drastically decreased [19,21,23], but the thyroid-stimu- …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have mainly examined reproductive functions [2][3][4] and the abnormalities of the thyroglobulin gene [1,9,10]. There has been no study investigating the pituitary-adrenal functions in the rdw rat, although hypothyroidism is known to cause adrenal dysfunction.…”
mentioning
confidence: 99%
“…Profiles of the limited digestion of proteins by peptidases were analyzed by the method originally developed by Cleveland et al [10] with some modification [11]. We have improved this method by burying protease(s) homogeneously in stacking gels electrophoretically prior to loading gel pieces in which a protein to be analyzed was present.…”
Section: Peptide Mappingmentioning
confidence: 99%